2016
DOI: 10.1002/anie.201605130
|View full text |Cite
|
Sign up to set email alerts
|

Combination of a Cyano Migration Strategy and Alkene Difunctionalization: The Elusive Selective Azidocyanation of Unactivated Olefins

Abstract: A conceptually new, efficient, and metal-free approach for the challenging azidocyanation of unactivated alkenes is presented. The strategy of intramolecular distal cyano migration is combined with alkene difunctionalization for the first time. A variety of useful azido-substituted alkyl nitriles are prepared in good yields and, most importantly, with exquisite regio- and stereo-selectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
62
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 210 publications
(63 citation statements)
references
References 67 publications
1
62
0
Order By: Relevance
“…There are also a few examples reported with distal aryl migration . Recently, we consecutively studied the migratory aptitude of cyano, heteroaryl, imino, formyl, and alkynyl groups, and demonstrated their applications in difunctionalization of unactivated alkenes. For example, we have disclosed the trifluoromethylative heteroarylation of alkenes for the first time (Scheme A) .…”
Section: Methodsmentioning
confidence: 99%
“…There are also a few examples reported with distal aryl migration . Recently, we consecutively studied the migratory aptitude of cyano, heteroaryl, imino, formyl, and alkynyl groups, and demonstrated their applications in difunctionalization of unactivated alkenes. For example, we have disclosed the trifluoromethylative heteroarylation of alkenes for the first time (Scheme A) .…”
Section: Methodsmentioning
confidence: 99%
“…disclosed an interesting intramolecular cyanide‐transfer process during the addition of Cl 3 CCN to an olefin, catalyzed by a copper complex. Zhu et al . and Liu et al .…”
Section: Introductionmentioning
confidence: 98%
“…Unfortunately,the desired product was either not observed at all or only formed in trace amounts (Table 3). Then, the PhI(OAc) 2 /TMSN 3 system that was reported for non-enantioselective azidocyanation by the groups of Wang [13] and Zhu [14] was surveyed in the presence of Cu I /L6.W ew ere delighted to find that the desired product 3a was obtained in 41 %y ield with 70 % ee.F urther ligand screening indicated that excellent enantioselectivity (95 % ee)c ould be achieved with the chiral bis(oxazoline) ligands L9 and L10,which both [a] All reactions were run on 0.4 mmol scale in CH 2 Cl 2 (2 mL). Yields of isolated products are given.…”
mentioning
confidence: 99%